2018
DOI: 10.1159/000488739
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Long Non-Coding RNA LINC00963 on Renal Interstitial Fibrosis and Oxidative Stress of Rats with Chronic Renal Failure via the Foxo Signaling Pathway

Abstract: Background/Aims: Chronic renal failure (CRF) is usually associated with chronic diseases such as congestive heart failure and diabetes mellitus, the prevalence of which is increased with age. This study is designed to investigate the role of long intergenic non-coding RNA (lincRNA) LINC00963 in renal interstitial fibrosis (RIF) and oxidative stress (OS) of CRF via the forkhead box O (FoxO) signaling pathway. Methods: Microarray data and annotated probe files related to CRF were downloaded by retrieving Gene Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Differentially expressed lnRNAs are determined in MI and co‐expressed with differentially expressed mRNAs, and their interactions are implicated in pathogenesis mechanism of MI . Silencing of ATP2B1‐AS1 can suppress renal interstitial fibrosis and oxidative stress in chronic renal failure . In this study, mouse ATP2B1‐AS1 silencing was suggested to inhibit the cardiomyocyte apoptosis and inflammation, suggesting a potential of ATP2B1‐AS1 in protection against MI.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Differentially expressed lnRNAs are determined in MI and co‐expressed with differentially expressed mRNAs, and their interactions are implicated in pathogenesis mechanism of MI . Silencing of ATP2B1‐AS1 can suppress renal interstitial fibrosis and oxidative stress in chronic renal failure . In this study, mouse ATP2B1‐AS1 silencing was suggested to inhibit the cardiomyocyte apoptosis and inflammation, suggesting a potential of ATP2B1‐AS1 in protection against MI.…”
Section: Discussionmentioning
confidence: 63%
“…Long non‐coding RNAs (lncRNAs) constitute a group of non‐coding RNAs implicated in diverse biological processes through regulation of gene expression and have recently been reported to be novel predictors in the setting of AMI . ATPase plasma membrane Ca 2+ transporting 1 antisense RNA 1 (ATP2B1‐AS1), also named long intergenic non‐protein‐coding RNA 936 (LINC00936), has been found to be an important regulator in chronic renal failure‐induced renal interstitial fibrosis and oxidative stress . However, the relationship between this lncRNA and MI remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [68] reported that LINC00963 was highly expressed in CRF rats, and FoxO3 was verified as a target gene of LINC00963. Lower LINC00963 expression attenuated interstitial fibrosis and oxidative stress in chronic renal failure (CRF) by activation of the FoxO signaling pathway, which helps us to understand the potential gene mechanisms of CRF, and may provide new prognostic markers for 8 of 14 CRF treatment in the future.…”
Section: Linc00936mentioning
confidence: 99%
“…Lower LINC00963 expression attenuated interstitial fibrosis and oxidative stress in chronic renal failure (CRF) by activation of the FoxO signaling pathway, which helps us to understand the potential gene mechanisms of CRF, and may provide new prognostic markers for 8 of 14 CRF treatment in the future. However, they did not thoroughly investigate how LINC00963 affects the activation of the FoxO signaling pathway and the potential mechanism in interstitial fibrosis CRF [68].…”
Section: Linc00936mentioning
confidence: 99%
“…Xie et al reported lncRNA H19 overexpression promoted renal fibrosis [70]. Chen et al characterized downregulation of an intergenic lncRNA LINC00963, which suppresses RIF (renal interstitial fibrosis) and OS (oxidative stress) of CRF (chronic renal failure) through activation of the FoxO (forkhead box O) signaling pathway [71]. Zhou et al demonstrated that lncRNA HOTAIR participated in renal interstitial fibrosis through upregulating miR-124 to block Notch1 pathway [72].…”
Section: Renal Fibrosis / Chronic Kidney Diseasementioning
confidence: 99%